Landscape changes based on sedimentological and geochemical studies in the region of Brudzeń Duży - Smolska, Ewa; Szwarczewski, Piotr (Miscellanea geographica, 2014)
Sedimentological and geochemical research carried out in North- West Mazovia, central Poland, allowed the determination of landscape transformation in relation to the history of human settlement. The types of sediments subject to analysis included palaeochannel filling, accumulation on the river floodplain and colluvial deposits. The absolute ages of sediments and their sedimentological features allow the conclusion that the first response to human activity in the area is recorded in the overbank deposits in the Skrwa River valley as a result of the Wielbarska Culture in 200-300 AD. Subsequently, fan accumulation at the mouths of gullies started around the 12 th -13 th centuries AD. Frequent changes of sediment properties have been observed since the early Middle Ages. The subsequent anthropogenic impact on homogenous deposits is recorded in increased heavy metal concentration in vertical geological profiles.